Do You See What I See? A Simulation Analysis of Order Bundling within a Transparent User Network in Geographic Space. Issue 1 (13th February 2020) - Ambra, Tomas; Caris, An; Macharis, Cathy
Abstract : The Physical Internet (PI) concept presents a radical change with the aim to revert the unsustainable practices that are used for transporting goods. It identifies dedicated freight flows and transforms them into transparent open logistics networks which can be accessed by other users, such as shippers and carriers. In this paper, we test the universal network openness in which the users can tap into the PI network and place orders that will be assigned to the nearest available transport service and consequently delivered to the order sender. The objective of our paper is to investigate the impact of inserting extra service points into existing dedicated freight flows of a service‐driven company. We simulate different transparency levels and routings to new pickup locations and evaluate the impact in terms of altered lead times, covered distances, and fill rates. The novel aspects presented herein are (1) deliveries based on decentralized location detection of the nearest order sender, (2) dynamically changing speed parameters of agents within specific geographic clusters based on their geo‐locations in order to account for congestion levels, (3) more realistic routing strategies that consider the urban layout, and (4) transparent querying of nearest agents in space and time that meet specific conditions such as current ongoing processes, available capacity, and position. Finally, we identify the impact from a general/holistic perspective that emerges once extra orders are assigned to the service‐driven company's fleet.